Construction of an instrumented roller ski and validation of three-dimensional forces in the skating technique - Hoset, M.; Rognstad, A. B.; Rølvåg, T.; Ettema, G.; Sandbakk, O. (Sports Engineering, 2014)
The purposes of the present investigation were to construct an instrumented roller ski, validate the force measurements and resolve the forces into three dimensions. To demonstrate the practical applications of the system, this study aimed to distinguish cycle characteristics and kinetics between skiers with different technical characteristics and between skating with and without poling while roller ski skating on a treadmill. It was shown that a roller ski with full bridge strain gauges could provide valid measurements of one-dimensional forces. By recording the orientation of the skis in space using the Qualisys motion capture system, the one-dimensional forces were converted into three dimensions according to the global coordinate system. However, some corrections are still required to obtain valid three-dimensional forces. It was possible to distinguish clear differences in cycle characteristics and roller ski forces between the two skiers with different characteristics and between skating with and without poling. Overall, this instrumented roller ski can be useful for future research and when monitoring elite athletes` technical development.